Laboratory investigation on early-age shrinkage cracking behavior of partially continuous reinforced concrete pavement. (9th May 2023) - Liu, Kaixiang; Zhang, Xiao; Wang, Yongbao; Han, Shujie; Luo, Zhili; Hao, Jiahang; Zhang, Jiacheng
Highlights: A rigid pavement structure called partially continuous reinforced concrete pavement (PCRCP) is proposed. The early-age shrinkage cracking behavior of PCRCP is analyzed through experiment and numerical analysis. The early-age behavior of PCRCP is improved than CRCP and ARCP. There is a coupling relationship between temperature and humidity. Active crack induction of PCRCP improves early-age cracking behavior significantly. Abstract: As a form of durable pavement structure commonly used in the world, continuously reinforced concrete pavement (CRCP) has prominent problems caused by irregular crack distribution in the early stage. According to the characteristics of the discontinuous distribution of CRCP longitudinal steel bar stress and active crack control method, a rigid pavement structure called partially continuous reinforced concrete pavement (PCRCP) was proposed to simultaneously optimize the crack distribution pattern and reduce the longitudinal steel ratio in this paper. Since early-age shrinkage cracking behavior is a key factor affecting its durability. This paper purposes to assess the early-age shrinkage cracking behavior of PCRCP by comparing different reinforcement methods in laboratory experiments. Research results indicated that the early-age shrinkage behavior of PCRCP is basically the same as that of CRCP. The early-age shrinkage behavior of PCRCP is significantly improved than the advanced reinforced concrete pavement (ARCP). Restricted by the boundary and longitudinal steel bars system, the concrete beam produces a top-down nonlinear temperature and humidity gradient, resulting in various degrees of shrinkage deformation at different depths inside. The active crack control method can control the early-age concrete slab to form uniform crack pattern with straight lines or fewer bending cracks, which improves early-age cracking behavior significantly. This paper is to further deepen and develop the theory of CRCP early-age cracking behavior and provide basic theory support for the subsequent experimental section studies of PCRCP.